2018
DOI: 10.1111/tran.12266
|View full text |Cite
|
Sign up to set email alerts
|

The right to be weary? Endurance and exhaustion in austere times

Abstract: This paper seeks to advance understandings of austerity's everyday affects by examining how neoliberal welfare retrenchment is lived, experienced and resisted. Drawing on interviews with young people in housing need, we demonstrate the ways in which day‐to‐day coping with welfare reform can lead to a state of fatigue, a gradual slow wearing‐out that comes with having to endure everyday hardship. Such weariness, we argue, is an integral part of understanding the everyday impacts of austerity. Yet despite the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 71 publications
0
55
0
Order By: Relevance
“…Yet by reinforcing the point that analyses of resistance depend on perspective we feel confident that our findings provide a foundation upon which others can build. In particular, Wilkinson and Ortega‐Alcazar’s () work on the political potential of weariness and resistance resonates for its relevance to challenges that our caregivers face. Such emerging conceptualisations of resistance underscore that there is still much to explore on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Yet by reinforcing the point that analyses of resistance depend on perspective we feel confident that our findings provide a foundation upon which others can build. In particular, Wilkinson and Ortega‐Alcazar’s () work on the political potential of weariness and resistance resonates for its relevance to challenges that our caregivers face. Such emerging conceptualisations of resistance underscore that there is still much to explore on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Recent and emerging writings regarding financial crisis and austerity make the case for deeper understandings of impacts at the personal scale, with individuals, families, and households simultaneously affected in multiple ways (Elwood & Lawson, ; García‐Lamarca & Kaika, ; Horton, ). Such work, on “subjective experiences” and personal responses to financial crisis and austerity (van Lanen, , p. 1605), has been conceptualised according to austerity urbanism, indebtedness, responsibilisation, embodiment, and financialisation (e.g., Fields, ; García‐Lamarca & Kaika, ; Stenning, ; Wilkinson & Ortega‐Alcázar, ), to name but a few. Austerity is also acknowledged as exacerbating everyday social differences and inequalities (Christophers, ; Fields, ; van Lanen, ), with emerging personalising, stigmatising discourses that “situate some people and places as sympathetic and deserving of help and others not” (Elwood & Lawson, , p. 104).…”
Section: Crisis Conjuncture and Everyday Lifementioning
confidence: 99%
“…For instance, van Lanen's study of disadvantaged urban youth in Ireland found austerity “directly and indirectly narrows the lifeworld” (, p. 1607) for this group. In research based in the north of England, Pimlott‐Wilson found significant emotional burdens and negotiations for young people who “acknowledge their own responsibility as future adult citizens” (, p. 288; also see Wilkinson & Ortega‐Alcázar, ). Further research on generational inequality by Christophers (), Hochstenbach (), and MacLeavy and Manley (, p. 1438) reveals the intergenerational transmission of inequality, “embedded over time” and across the lifecourse, leading to socio‐economic polarisations.…”
Section: Crisis Conjuncture and Everyday Lifementioning
confidence: 99%
See 2 more Smart Citations